2018
DOI: 10.3221/igf-esis.47.15
|View full text |Cite
|
Sign up to set email alerts
|

Hexagrid-Voronoi transition in structural patterns for tall buildings

Abstract: In this paper, a first insight into the role that non-conventional structural patterns might play in the design of tall buildings is presented. The idea is to explore the mechanical properties of selected non-conventional structural patterns, in the form of both regular (Hexagrid) and irregular (Voronoi tessellation inspired) arrays, in order to assess their actual applicability in tall building design. For this aim, the concept of Representative Volume Element (RVE) and a classical homogenization-based microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The nodes of a panel that lie on a RD preserve their mutual distance in the horizontal direction, thus affecting the relevant component of the strain in the plane of the panel and, consequently, the overall flexural stiffness of the grid. The arising stiffening effect is analogous to the confinement provided by the steel lamina on the rubber layers in a laminated elastomeric bearing, see in particular Montuori et al (2015) and Mele et al (2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nodes of a panel that lie on a RD preserve their mutual distance in the horizontal direction, thus affecting the relevant component of the strain in the plane of the panel and, consequently, the overall flexural stiffness of the grid. The arising stiffening effect is analogous to the confinement provided by the steel lamina on the rubber layers in a laminated elastomeric bearing, see in particular Montuori et al (2015) and Mele et al (2019).…”
Section: Resultsmentioning
confidence: 99%
“…This approach is especially conceived for regular patterns, in which the representative volume element is detected as the smallest basic cell that can tessellate the whole grid. Upon introduction of suitable correction factors, the same approach can be extended to irregular patterns, see in particular the Voronoi grids investigated in Angelucci and Mollaioli (2018) and Mele et al (2019). This method provides the designer with a sound and effective tool to cope both with conventional and innovative structural skins for tall buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Current state‐of‐the‐art methods adopt Voronoi tessellations (Angelucci & Mollaioli, 2018; Mele et al., 2019) that are derived from hexagonal honeycomb systems, the closest tessellation having a regular distribution of seeds. The seeds of this regular pattern are then perturbed by using three parameters, the random angle, the random scale factor, and the irregularity factor, which become the descriptors of the tessellation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the esthetic structure and the use of broken lines in the Voronoi diagram, it has gained the attention of architects for the design of modern buildings (Mele et al, 2019;Okabe et al, 2009). A notable example of a space structure inspired by the Voronoi structures is the Beijing National Blue Sports Center, known as the Blue Cube, which was the venue for swimming, diving, and water polo competitions at the Beijing Summer Olympics (Figure 2(c)).…”
Section: Introductionmentioning
confidence: 99%
“…It was indicated that under static loading, Voronoi tessellation was capable of resisting against lateral loading. Mele et al (2019) studied various regular and non-regular structural patterns such as Hexagrid and Voronoi tessellation in the design of tall buildings and discuss their capability as an efficient structural pattern for modern designs.…”
Section: Introductionmentioning
confidence: 99%